Structural Evaluation of Battery Module Profiles - Mohamed, Dayib; Ligmajer, Oskar (My University, 2023)
Developing battery packs that can sustain various loads with reduced material and manufacturing costs has become increasingly important in the current trend of electrifying transport vehicles to mitigate global greenhouse gas emissions. This master’s thesis aims to assist the cleantech company Reliefed AB in evaluating the structural analysis of their sandwich-structured battery module concept through detailed finite element modelling. The focus of the project is to investigate the durability and structural response of the battery module profiles. The study assesses how the battery module responds to bolt preload, shock, and random vibration loads during its usage. The analysis includes subjecting the battery to shock and random vibration loads in different directions. Additionally, the maximum normal tensile stresses and shear stresses of the modelled adhesive are analysed when the battery module is exposed to bolt preload and shock loads, to determine if they fall within the conductive adhesive’s material properties. Assumptions are made due to uncertainties regarding the material properties of different components in the module, module placement in the vehicle, and the types of loads impacting the module. The analysis results demonstrate promising findings based on the conducted analysis. Whilst further considerations, such as thermal effects and detailed modelling of other parts like the couplers between battery cells and the conductive adhesive, are necessary, it can be concluded that the concept is suitable to use for future developments of the battery pack.
Keywords: Battery; Battery Cell; Battery Module; Battery Pack; Electric Vehicle; Extruded Aluminum Profile; Sandwich-structure